The HACCP food safety manual - Loken, Joan K. (John Wiley & Sons, 1994)
This comprehensive yet simple-to-use guide is organized according to the logical Hazard Analysis Critical Control Points steps. Each step includes a short description, practical applications, supporting narratives, posters, charts and workbook projects to facilitate understanding. Features a section on foodborne illness containing training aids, food microbiology, preparing for and handling complaints. Illustrated throughout with flow charts and diagrams.